Obesity May Require a Higher Level of Trauma Care: A Propensity-Matched Nationwide Cohort Study. (20th April 2021) - Fu, Chih-Yuan; Bajani, Francesco; Bokhari, Marissa; Butler, Caroline; Starr, Frederick; Messer, Thomas; Kaminsky, Matthew; Tatebe, Leah C.; Dennis, Andrew; Schlanser, Victoria; Poulakidas, Stathis; Cheng, Chi-Tung; et al.
Abstract: Objective: Stable patients with less severe injuries are not necessarily triaged to high-level trauma centers according to current guidelines. Obese patients are prone to comorbidities and complications. We hypothesized that stable obese patients with low-energy trauma have lower mortality and fewer complications if treated at Level-I/II trauma centers. Methods: Blunt abdominal trauma (BAT) patients with systolic blood pressures ≥90mmHg, Glasgow coma scale ≥14, and respiratory rates at 10-29 were derived from the National Trauma Data Bank between 2013-2015. Per current triage guidelines, these patients are not necessarily triaged to high-level trauma centers. The relationship between obesity and mortality of stable BAT patients was analyzed. A subset analysis of patients with injury severity scores (ISS) <16 was performed with propensity score matching (PSM) to evaluate outcomes between Level-I/II and Level-III/IV trauma centers. Outcomes of obese patients were compared between Level-I/II and Level-III/IV trauma centers. Non-obese patients were analyzed as a control group using a similar PSM cohort analysis. Results: 48, 043 stable BAT patients in 707 trauma centers were evaluated. Non-survivors had a significantly higher body mass index (BMI) (28.7 vs. 26.9, p < 0.001) and higher proportion of obesity (35.6% vs. 26.5%, p < 0.001) than survivors. After a PSM (1, 502 obese patients: 751 in Level-I/II trauma centers and 751 in Level-III/IV trauma centers), obese patients treated in Level-I/II trauma centers had significantly lower complication rates than obese patients treated in other trauma centers (20.2% vs. 26.6%, standardized difference = 0.151). The complication rate of obese patients treated at Level-I/II trauma centers was 20.6% lower than obese patients treated at other trauma centers. Conclusion: Obesity plays a role in the mortality of stable BAT patients. Obese patients with ISS < 16 have lower complication rates at Level-I/II trauma centers compared to obese patients treated at other trauma centers. Obesity may be a consideration for triaging to Level-I/II trauma centers.